Arqueologia e coletivos indígenas : os purizados do entorno da Serra do Brigadeiro/Minas Gerais - Elisângela de Morais Silva (2011)
This essay aims to understand how relations between archaeology and indigenous collectives have been – and are – undertaken in Brazil. Through analyzing colonial / nationalrhetoric, fed by emerging sciences, it is possible to recognize the effort to make us believe on the conquest fantasy – on the annihilation or on the complete disappearance of some indigenous groups. I selected as a case studythe group called Puri, considered extinct until some time ago. Despite the colonial desire for subsumption of indigenous peoples, dozens of collectives around the Brigadeiro moundshave come to recognize in themselves an indigenous background, under the term of a purized (purizada) person. Under this context, another aim of this work is to establish a relationship of dialogue and collaboration with the purized people of the Graminha communitie and Araponga, through a relational archaeology, seeking to understand their relations with the archaeological discourse and with the material culture. Among these people, it is noticeable the (re)production of costumes and objects, which in the local opinion referred to the ancient Puri. Regarding the (re)production of objects, the specificity of this study lays on the artisan work, whose prime-matter is coffee straw. The product of artisan work, as material culture produced in congruence with ancient knowledge and in contact with local contexts, is simultaneously an object of identification, of identity materialization and, also, of temporal and spatial continuity.